Mission hurricane - Goebel, Jenny (New York, NY : Scholastic Inc., 2016)
Amy and Dan are shocked to learn that Outcast, a violent renegade who is threatening the lives of innocent people, may be a Cahill family member who is determined to exact revenge.
Keywords: Brothers and sisters -- Fiction; Revenge -- Fiction; Adventure and adventurers -- Fiction; Siblings -- Fiction; Revenge -- Fiction; Adventure fiction